Enhancing the experience of remote lectures: Development of a new digital software to meet the needs of educators and students in higher education - Hansson, Moa; Widdgård, Thea (My University, 2021)
The pandemic Covid-19 has forced many high-level educational institutions to shift from traditional to remote lectures. Current software used for remote live lectures in higher education are primarily designed to facilitate business meetings. However, literature examining students' and educators' experiences using the software suggests that there is a need for a more adapted design. This paper examines the needs of educators and students and proposes an initial concept of a software designed with consideration of the findings. Furthermore, theories within the areas of cognitive ergonomics, user experience design, interaction design and design for usability have been applied. The concept is based on user studies consisting of 2 surveys, 10 interviews and 4 usability tests. The final concept improves the quality of communication, interaction and collaboration of remote live lectures and provides users with an enhanced user experience compared to the current solutions.
Keywords: : Online live lectures; Higher education; Cognitive ergonomics; User experience design; Interaction design; Design for Usability